EFL oral skills development : A thematic analysis of teaching methods used in EFL teaching in Finland - Järvinen, Anna (My University, 2021)
Oral skills are an essential part of language learning but due to their complexity, it is challenging to teach them. Teaching oral skills includes teaching interaction skills, text production skills and text interpretation skills (Finnish National Agency for Education 2014, 220). The present Master’s thesis aims to provide information and tools for all foreign language teachers to use in teaching oral skills. What are effective teaching methods for oral skills development? How are oral skills taught in Finnish language education? What makes the oral exercises effective? These research questions are answered through a review of research literature and thematic analysis of the teacher's reflections on their oral skills teaching methods. Especially the third research question which focuses on teachers’ reflections brings new insights into oral skills teaching. A qualitative study was conducted to discover what kind of oral exercises are used by language teachers in Finland. Seven teachers of English participated in this study for one week. Teachers were asked to reflect on the oral exercises they had used and write down what made them effective. A reflective form inspired by the narrative frame was provided for the teachers to guide their reflections. Language as a means of communication is a learning goal in many teaching objectives (for instance Finnish National Agency for Education, Common European Framework of Reference). Researchers agree that a combination of explicit teaching and authentic language use has a positive effect on oral skills development. Based on this study, oral exercises where learners produced ready-made text, such as listen and repeat and reading aloud, were most used by the English teacher participants. There were also exercises where learners used authentic language, such as role plays and word describing games. Learners' positive learning experience (relaxed atmosphere in class, high participation rate, learners' positive attitude) and teachers' positive teaching experience (versatility and easiness of exercises) both indicated effectivity for the teachers. Exercises that practiced pronunciation or strengthened vocabulary were considered effective for oral skills development as well. Other sign of effectiveness was feedback from the students. In conclusion, language production is taught a lot but teaching interaction skills and giving opportunities for authentic language use should increase. This study is relatively small but offers us a glimpse of the teaching methods used to teach oral skills in Finland. Especially teachers' rationale about the effectiveness of used exercises gives us interesting insights that are not mentioned in research literature. It was also fascinating, how pronunciation and vocabulary were taught via common oral exercises such as listen and repeat or read aloud, whereas grammar was taught through other, more uncommon oral exercises. In the future, a similar type of study but on a bigger scale and for a prolonged time would be fruitful.
Keywords: oral skills development, teaching oral skills, teaching EFL